Answer:
go on photomath
Step-by-step explanation:
Step-by-step explanation:
hope I understand your qyestion
Equation 1 : R+G=20
Equation 2 : 7R+3G=9
Multiply Equation by 3, it becomes
3R+3G=60 ...... Equation 3
Now Equation 3 minus Equation 2
-4R = 51
R = - 51/4
Sub R into Equation 1, you can find G
Answer:
The correct answer is - A. cultural.
Step-by-step explanation:
The exchange of music, thus creating an artistic and entertainment connection between the people of different countries, regions, or continents is a nice example of cultural connection.
The music is part of the culture of the people, and all the people from every part of the world have their own specific type of music that complements their culture.
With the globalization process, people have been able to see and hear things from all around the world, thus managing to hear the music of all pats of the world. The Japanese and Korean music have experienced a real ''boom'' in popularity in the western world, as lot of people find it interesting, and the American music also reached new countries where it became the most popular, like in Europe for example.
MARK ME BRAINLIEST PLEASE!!! :) HOPE IT HELPS
Answer with Step-by-step explanation:
We are given that
![W(t)=W_0(1.90)^t](https://tex.z-dn.net/?f=W%28t%29%3DW_0%281.90%29%5Et)
Where t corresponds to the year 2000=0
a.![W(0)=2540MW](https://tex.z-dn.net/?f=W%280%29%3D2540MW)
Substitute the values
![2540\times 10^6=W_0(1.90)^0=W_0](https://tex.z-dn.net/?f=2540%5Ctimes%2010%5E6%3DW_0%281.90%29%5E0%3DW_0)
![W_0=2540MW](https://tex.z-dn.net/?f=W_0%3D2540MW)
b.In 2004
t=4
![W(4)=2540(1.90)^4](https://tex.z-dn.net/?f=W%284%29%3D2540%281.90%29%5E4)
![W(4)=33101.534 MW](https://tex.z-dn.net/?f=W%284%29%3D33101.534%20MW)
c.In 2013
t=13
![W(13)=2540(1.9)^{13}=10.68\times 10^6MW](https://tex.z-dn.net/?f=W%2813%29%3D2540%281.9%29%5E%7B13%7D%3D10.68%5Ctimes%2010%5E6MW)
Answer:
-6
Step-by-step explanation:
r = 9, b = 5, g = -6
Plug these values into (r + b - 8)(b + g)
[(9) + (5) - 8]*[(5) + (-6)]
Combine like terms in the brackets
[6]*[-1]
6 times -1 equals -6, so that is your answer